2018
DOI: 10.1038/s42003-018-0062-2
|View full text |Cite
|
Sign up to set email alerts
|

Selective cold pain inhibition by targeted block of TRPM8-expressing neurons with quaternary lidocaine derivative QX-314

Abstract: Treatment of pain with local anesthetics leads to an unfavorable decrease in general sensory acuity due to their indiscriminate block of both pain sensing (nociceptors) and non-pain sensing nerves. However, the cell impermeant lidocaine derivative QX-314 can be selectively targeted to only nociceptors by permeation through ligand-gated cation channels. Here we show that localized injection of QX-314 with agonists for the menthol receptor TRPM8 specifically blocks cold-evoked behaviors in mice, including cold a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Control animals received an equivalent volume of the vehicle. To determine the induction of CIPN, we tested these animals sensitivity to thermal (heat and cold) and mechanical stimuli at 3, 10, and 15 days after the initial Paclitaxel injection 26,27 . B6 mice exhibited mechanical allodynia (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Control animals received an equivalent volume of the vehicle. To determine the induction of CIPN, we tested these animals sensitivity to thermal (heat and cold) and mechanical stimuli at 3, 10, and 15 days after the initial Paclitaxel injection 26,27 . B6 mice exhibited mechanical allodynia (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To measure cold sensitivity of the hind paws, the cold plantar assay was performed as previously described 27,55 . Briefly, mice were allowed to acclimate in Plexiglas chambers for 2 hours prior to cold plantar testing performed at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the TRPA1 channel is activated by a variety of environmental irritants and is related to chemical-evoked pain, the contribution of the TRPA1 channel for detecting noxious mechanical and noxious cold pain is still controversial [ 35 ]. Previous studies have shown that QX-314 enters the cell through the TRP channels and increases mechanical, heat, and cold pain thresholds by blocking sodium channels in vivo [ 23 , 26 , 36 ]. Kobayashi et al [ 35 ] reported that approximately 66.7% of TRPV1-expressing DRG neurons co-express TRPA1 channels, and 100% of TRPA1-expressing DRG neurons co-express TRPV1 channels.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic deletion of TRPM8 in mice revealed that this channel is important for sensing moderately cold temperatures [6][7][8]. Later studies showed that the channel is also involved in pathological cold sensation [9,10].…”
Section: Introductionmentioning
confidence: 99%